Machine learning for all : Practical steps using MATLAB - Abdullah, Abdul Rahim; Shair, Ezreen Farina; Kandaya, Shaarmila; Rahman, Kazi Ashikur (Penerbit UTeM Press, 2025)
This book, Machine Learning for All: Practical Steps Using Matlab, is written for anyone who wants to learn how to apply machine learning using MATLAB. Whether you're new to machine learning or already have some experience, this guide will walk you through the key concepts and show you how to implement them with clear, easy-to- follow examples. By the end of this book, you'll have a solid understanding of machine learning and be confident in applying these techniques in MATLAB to solve real-world problems.